Maintenance system in Section 18 PPP (an analysis) / Azman Ahmad and Shahrin Shah Abdul Rahman - Ahmad, Azman; Abdul Rahman, Shahrin Shah (1990)
This project report is a study of a maintenance system and divided into five chapters. The first chapter contains all the relevant information concerning the topic and the second chapter gives an outline of the existing system. With the help of figures an charts in the Appendices, a rough idea can be obtained on the current situation. The third chapter is a continuation of the second where an understanding of the problems and the problem they encounter can be obtained. Suggestions to improve the existing system are the contents of the four chapter and the conclusion of the study is mentioned in the final chapter.